Optical Phase Alteration in Nonlinear Fiber Bragg Grating - Rawat, Poornima; Pawar, Santosh; Hiwarkar, Tryambak (International Journal of Computer Sciences and Engineering, 2019)
The optical phase characteristics of fiber Bragg grating is studied under the influence of the Kerr nonlinearity. The expression of optical phase has been obtained analytically under nonlinear regime using coupled mode theory. The optical phase is studied by plotting the phase factor as a function of wavelength at various input intensities. The results show that the phase of the propagating beam is altered after specific excitation intensity. Such variation in the optical phase of beam can be utilizing the grating as a nonlinear device for optical phase modulator in all optical signal processing.